Effect of total body irradiation lung block parameters on lung doses using three‐dimensional dosimetry. Issue 4 (5th January 2022) - Luk, Samuel M. H.; Wallner, Kent; Glenn, Mallory C.; Ermoian, Ralph; Phillips, Mark H.; Tseng, Yolanda D.; Kim, Minsun
Abstract: Purpose: Total body irradiation (TBI) is an integral part of stem cell transplant. However, patients are at risk of treatment‐related toxicities, including radiation pneumonitis. While lung dose is one of the most crucial aspects of TBI dosimetry, currently available data are based on point doses. As volumetric dose distribution could be substantially altered by lung block parameters, we used 3D dosimetry in our treatment planning system to estimate volumetric lung dose and measure the impact of various lung block designs. Materials and methods: We commissioned a TBI beam model in RayStation that matches the measured tissue‐phantom ratio under our clinical TBI setup. Cerrobend blocks were automatically generated in RayStation on thoracic Computed Tomography (CT) scans from three anonymized patients using the lung, clavicle, spine, and diaphragmatic contours. The margin for block edge was varied to 0, 1, or 2 cm from the superior, lateral, and inferior thoracic borders, with a uniform margin 2.5 cm lateral to the vertebral bodies. The lung dose was calculated and compared with a prescription dose of 1200 cGy in six fractions (three with blocks and three without). Result: The point dose at midplane under the block and the average lung dose are at the range of 73%–76% and 80%–88% of prescription dose respectively regardless of the block margins. In contrast, the percent lung volume receiving 10 Gy increased by nearly two‐fold, from 31% to 60% over the margins from 0 to 2 cm. Conclusions: The TPS‐derived 3D lung dose is substantially different from the nominal dose assumed with HVL lung blocks. Point doses under the block are insufficient to accurately gauge the relationship between dose and pneumonitis, and TBI dosimetry could be highly variable between patients and institutions as more descriptive parameters are not included in protocols. Much progress remains to be made to optimize and standardize technical aspects of TBI, and better dosimetry could provide more precise dosimetric predictors for pneumonitis risk.